METODE PENYELESAIAN MASALAH CAUCHY DEGENERATE NONHOMOGEN MELALUI PENYELESAIAN MASALAH CAUCHY NONDEGENERATE NONHOMOGEN - hariyanto, Susilo (MATEMATIKA, 2008)
In this article, we investigate how to solve abstract degenerate Cauchy problems nonhomogen via abstract nondegenerate Cauchy problems nonhomogen. The problem are discussed in the Hilbert space H  which can be written as an orthogonal direct sum of Ker M and . Under certain assumptions it is possible to reduce the problems to an equivalent  nondegenerate Cauchy problem in the factor space   H/Ker M  which can be easier to solve. Moreover we defines an operator ZA which maps the solutions of abstract nondegenerate Cauchy problems nonhomogen to abstract degenerate Cauchy problems nonhomogen